2013
DOI: 10.1177/000348941312200904
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Phonation Threshold Power in Normal and Disordered Voice Production

Abstract: Objectives Phonation threshold pressure (PTP) and phonation threshold flow (PTF) are useful aerodynamic parameters, but each is sensitive to different disorders. A single comprehensive aerodynamic parameter sensitive to a variety of disorders might be beneficial in quantitative voice assessment. We performed the first study of phonation threshold power (PTW) in human subjects. Methods PTP and PTF were measured in 100 normal subjects, 19 subjects with vocal fold immobility, and 94 subjects with a benign mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Alternative aerodynamic parameters more suited for atrophy patients could be the phonation threshold pressure (PTP) and phonation threshold flow (PTF) reflecting the minimum pressure and flow required to sustain phonation. These parameters may better mirror the ease of phonation [ 28 ] [personal communication S. Thibeault and D. Phyland]. Frame-by-frame analysis (FBFA) of laryngovideostroboscopy in which subject’s average percentage of closed frames per glottic cycle is recorded may be another option [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alternative aerodynamic parameters more suited for atrophy patients could be the phonation threshold pressure (PTP) and phonation threshold flow (PTF) reflecting the minimum pressure and flow required to sustain phonation. These parameters may better mirror the ease of phonation [ 28 ] [personal communication S. Thibeault and D. Phyland]. Frame-by-frame analysis (FBFA) of laryngovideostroboscopy in which subject’s average percentage of closed frames per glottic cycle is recorded may be another option [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jiang and Tao then proposed another aerodynamic parameter, PTF, which is defined as the minimum airflow necessary to initiate vocal fold vibration [22]. PTP is a better descriptor of vocal fold viscoelasticity, whereas PTF is a better descriptor of vocal fold width [23]. Thus, PTP and PTF are irreplaceable landmarks in the aerodynamic assessment of laryngeal function [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the changes in vocal fold stiffness and mass, it can be speculated that oscillation patterns would change, not only with regard to the ƒ o range, but also under different loudness conditions. In this context, it has been shown that the phonation threshold pressure increased in patients with vocal fold mass lesions and decreased after phonomicrosurgery [ 19 , 20 ]. However, greater loudness could itself have an effect on vocal fold oscillation patterns.…”
Section: Introductionmentioning
confidence: 99%